2021
DOI: 10.1007/s10456-021-09812-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the prolyl isomerase Pin1 improves endothelial function and attenuates vascular remodelling in pulmonary hypertension by inhibiting TGF-β signalling

Abstract: Pulmonary arterial hypertension (PAH) is a devastating disease, characterized by obstructive pulmonary vascular remodelling ultimately leading to right ventricular (RV) failure and death. Disturbed transforming growth factor-β (TGF-β)/bone morphogenetic protein (BMP) signalling, endothelial cell dysfunction, increased proliferation of smooth muscle cells and fibroblasts, and inflammation contribute to this abnormal remodelling. Peptidyl-prolyl isomerase Pin1 has been identified as a critical driver of prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Nineteen studies were selected after applying the exclusion and inclusion criteria (Figure 1) [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. They were published between 2009 and 2022, providing data for twenty drugs and two combinations of two drugs, with a great variety of mechanisms of action (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies were selected after applying the exclusion and inclusion criteria (Figure 1) [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. They were published between 2009 and 2022, providing data for twenty drugs and two combinations of two drugs, with a great variety of mechanisms of action (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…All MCT animals were rats (Table 2) and a single MCT dose of 60 mg/Kg was administered, except in one study (30 mg/Kg) [16], to induce PH. In two studies, rats further underwent aortocaval shunt surgery (MCT + S) [19,31]. Other models underwent hypoxia periods: CH and SuHx (Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…TGFβ signaling pathway was overactivated and leads to excessive proliferation and resistance of apoptosis [ 27 , 28 ]. TGF-β1 is an essential regulator of extracellular matrix (ECM) deposition, promoting fibrosis and inflammation [ 29 ]. These studies confirmed that the immune response and inflammation play important roles in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Leppäranta et al [ 35 ] reported that LTBP1 was significantly upregulated inidiopathic pulmonary fibrosis (IPF) patient lungs and modulated TGF-β availability and activation in different pulmonary compartments in the fibrotic lung. TGFβ signaling pathway was overactivated in PAH and lead to excessive proliferation, the resistance of apoptosis and ECM deposition [ 29 , 30 ]. ECM deposition in remodeling pulmonary arteries is thought to be a key characteristic of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Pin1 has been found to act as a critical driver of vascular cell proliferation, apoptosis, and inflammation, with implication in many cardiovascular diseases (e.g., atherosclerosis, coronary restenosis, and cardiac hypertrophy) [ 10 , 11 , 12 ]. Notably, Pin1 has been reported to regulate the degradation of the inducible nitric oxide synthase (iNOS) in murine aortic endothelial cells upon induction by lipopolysaccharide and IFN-γ [ 13 ], as well as to interact with eNOS in a phosphorylation-dependent manner, thereby suppressing eNOS activity, similar to the tonic suppression of eNOS activity by caveolin-1 [ 14 ].…”
Section: The Role Of the Cis-trans Isomerase Pin1 In Vascular Endotheliummentioning
confidence: 99%